2002
DOI: 10.1381/096089202320995592
|View full text |Cite
|
Sign up to set email alerts
|

Liver Damage in Obese Patients

Abstract: In morbidly obese patients, the incidence of histological liver damage is very high, despite acceptable liver function tests. In addition to steatosis, however, a "second hit" to induce necrosis and inflammation, favoring the development of significant fibrosis, is not essential. Being obese is an independent risk factor for liver damage and could contribute to liver fibrosis either alone or in association with other insulting factors. The identification of obese patients with septal fibrosis/cirrhosis, at sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 11 publications
0
38
0
3
Order By: Relevance
“…Although the pathogenesis of NAFLD remains poorly understood, NAFLD is strongly associated with metabolic syndrome, a wellestablished clinical constellation of central obesity, type-2 diabetes mellitus, arterial hypertension, and dyslipidemia [2,[19][20][21]. The strong association of obesity with NAFLD suggests that obesity contributes to the pathogenesis of liver injury by steatosis and progression to steatohepatitis [2,20,22,23]. The prevalence of NAFLD and non-alcoholic steatohepatitis (NASH) in obese patients ranges from 69-100% to 25-30% of cases, respectively [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of NAFLD remains poorly understood, NAFLD is strongly associated with metabolic syndrome, a wellestablished clinical constellation of central obesity, type-2 diabetes mellitus, arterial hypertension, and dyslipidemia [2,[19][20][21]. The strong association of obesity with NAFLD suggests that obesity contributes to the pathogenesis of liver injury by steatosis and progression to steatohepatitis [2,20,22,23]. The prevalence of NAFLD and non-alcoholic steatohepatitis (NASH) in obese patients ranges from 69-100% to 25-30% of cases, respectively [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…This study discussed the correlation of risk factors like dietary composition, medications & BMI in association with NAFLD.NAFLD was diagnosed in patients who initially came to medical attention by the incidental findings of increased liver echogenecity during ultrasonography done for master health checkup &other reasons. Ultrasonography could be used as aeconomical, non-invasive predictor of liver histology inmild, moderate and severe steatosis with acceptable sensitivity and specificity (10,11) . 67(84.8%) patients of our study population shown to have Grade I (mild) fatty changes of liver in ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 75% of patients with type II diabetes mellitus and over 50% of patients with a history of myocardial infarct have NAFLD [31,42,43]. Many patients undergoing bariatric surgery will also have NAFLD [44][45][46]. With the rapidly increasing prevalence of obesity and diabetes [13,15], the overall number of patients who will develop NAFLD will only increase.…”
Section: Discussionmentioning
confidence: 99%